FIQH SOSIOKULTURAL UNTUK MENEGAKAN NILAI KEMANUSIAAN UNIVERSAL - Muhammad Syarif; Bustamam Usman (STISNU Aceh, 2023)
Re-reading the thinking products of classical scholars, especially on Islamic law (fiqh studies) is a very important thing, because the results of human thought are inseparable from the socio-cultural aspects that surround it. The concept of reforming Islamic law must be based on the spirit of grounding Islamic law within the framework of implementation and regulation through legislation. The use of a multidisciplinary methodology and approach in establishing a law is of course a matter of great urgency. With the elaboration of classical methodology and a modern scientific approach, it will produce an objective, humanist and progressive study of fiqh. There are many factors that influence the birth of fiqh books. These aspects are directly related to the life of the scholars, so they have a connection in forming their horizons of thinking. These aspects include; a) politics, b) culture, and c) social community. This product of thought is used as a tool to address religious issues which have dimensions of worship, muamalah, family law, civil and criminal law. The socio-cultural approach has made a major contribution to methodological enrichment, theoretical enlightenment, and the paradigmatic development of fiqh. So that the study of Islamic law that develops really makes a meaningful contribution to the upholding of universal human values.